Osseointegration of implant surfaces in metabolic syndrome and type‐2 diabetes mellitus - Bergamo, Edmara T. P.; de Oliveira, Paula G. F. P.; Campos, Tiago M. B.; Bonfante, Estevam A.; Tovar, Nick; Boczar, Daniel; Nayak, Vasudev Vivekanand; Coelho, Paulo G.; Witek, Lukasz (Journal of biomedical materials research. Part B, Applied biomaterials, 2024)
This in vivo study evaluated the bone healing response around endosteal implants with varying surface topography/chemistry in a preclinical, large transitional model induced with metabolic syndrome (MS) and type‐2 diabetes mellitus (T2DM). Fifteen Göttingen minipigs were randomly distributed into two groups: (i) control (normal diet, n = 5) and (ii) O/MS (cafeteria diet for obesity induction, n = 10). Following obesity induction, five minipigs from the obese/metabolic syndrome (O/MS) group were further allocated, randomly, into the third experimental group: (iii) T2DM (cafeteria diet + streptozotocin). Implants with different surface topography/chemistry: (i) dual acid‐etched (DAE) and (ii) nano‐hydroxyapatite coating over the DAE surface (NANO), were placed into the right ilium of the subjects and allowed to heal for 4 weeks. Histomorphometric evaluation of bone‐to‐implant contact (%BIC) and bone area fraction occupancy (%BAFO) within implant threads were performed using histomicrographs. Implants with NANO surface presented significantly higher %BIC (~26%) and %BAFO (~35%) relative to implants with DAE surface (%BIC = ~14% and %BAFO = ~28%, p < .025). Data as a function of systemic condition presented significantly higher %BIC (~28%) and %BAFO (~42%) in the control group compared with the metabolically compromised groups (O/MS: %BIC = 14.35% and %BAFO = 26.24%, p < .021; T2DM: %BIC = 17.91% and %BAFO = 26.12%, p < .021) with no significant difference between O/MS and T2DM ( p > .05). Statistical evaluation considering both factors demonstrated significantly higher %BIC and %BAFO for the NANO surface relative to DAE implant, independent of systemic condition ( p < .05). The gain increase of %BIC and %BAFO for the NANO compared with DAE was more pronounced in O/MS and T2DM subjects. Osseointegration parameters were significantly reduced in metabolically compromised subjects compared with healthy subjects. Nanostructured hydroxyapatite‐coated surfaces improved osseointegration relative to DAE, regardless of systemic condition.